Macro accounting of the tourist cluster’s state regulation in Ukraine - Filshtein, L.; Malakhovskyi, Yu.; Zhovnovach, R.; Фільштейн, Л. М.; Малаховський, Ю. В.; Жовновач, Р. І. (Baltija Publishing, 2017)
The article summarizes the approaches and defines the prospects for using international experience in the organization of macroeconomic accounting in the sphere of state regulation of the development of the tourist cluster of the national economy of Ukraine. The classification and description of the main types of tourism expenditures, which are thoroughly considered in determining the contribution of tourism and travel to the gross value added and gross domestic product of the national economy, are given. It is substantiated the decisive influence of attracting international experience in development of a tourism satellite account (TSA) in the conditions of modernization of the forms of public administration development of the sectoral structure of the national economy for the implementation of the model of the postindustrial technological system of the management system. The point of view justified that it is necessary to further development of instrumental methods for the determination of the direct, indirect and indirect effects in the context of universal cost analysis and results of tourism. For the regional localization of accounting tourist activities at the subnational level in Ukraine proposed to apply interregional approach what based on zoning of TSA, or “strictly” regional approach.